Laboratory evaluation of Clusia fluminensis extracts and their isolated compounds against Dysdercus peruvianus and Oncopeltus fasciatus - Duprat,Rodrigo C. (2017)
ABSTRACT The effects of the hexanic extracts of the fruits and flowers of Clusia fluminensis Planch. & Triana, Clusiaceae, as well as their main constituents, the triterpene lanosterol and the benzophenone clusianone, were evaluated on hemipterans Dysdercus peruvianus and Oncopeltus fasciatus. The topical treatments of insects with the hexanic extracts significantly affected the survival of O. fasciatus, but not that of D. peruvianus. Concomitantly, extracts delayed the development of both hemipterans. Moreover, isolated lanosterol significantly reduced both the survival and development of O. fasciatus and D. peruvianus, while clusianone only reduce the survival of D. peruvianus and marginally inhibited the development of both insects. The results show the specific activity of lanosterol and clusianone against the two evaluated insect species and indicate the potential of compounds derived from C. fluminensis for the development of specific biopesticides for the control of agricultural pests. Subsequent work will examine the mode of action of lanosterol and clusianone isolates from C. fluminensis.